Vocabulary learning strategies : First-year EFL-LMD Student's case study universidad of Abd Elhamid ibn badis (Mostaganem) - SADEK, Rima (My University, 2013)
Learning a language entails learning its vocabulary. Nonetheless, vocabulary learning is considered as a common source of difficulty for foreign language learners (Meara, 1980; McCarthy, 1988). It has been highlighted as the most challenging obstacles that students have to overcome (Singleton, 1999; Schmitt, 2000). The present research is an exploratory case study that focuses on exploiting the vocabulary learning strategies that first year EFL LMD students frequently use and perceive useful to enlarge their repertoire. It also aims at showing the approaches they employ in order to promote their vocabulary acquisition. Seventy random under-graduate students were asked to fill in a questionnaire, were submitted to a survey and a vocabulary test. Besides to this, an examination of copies and classroom observation were done. Three pioneer theories are relied on to analyse the data gathered namely, Schmitt’s taxonomy (1997, 2000), Sanaoui classification (1995), and Clouston research (1996). The results show that vocabulary learning strategies are perceived as very useful by students though they are not often used. Concerning the approaches students adopt while learning vocabulary, the majority of them are classified under the unstructured approach which corresponds to what is referred as ‘poor learners’. In order to encounter these difficulties, some pedagogical implications are suggested to raise students’ autonomy towards using vocabulary learning strategies.
Keywords: Keywords: Vocabulary learning strategies, categories, field study, EFL learners.